A RARE LOCALIZATION OF INTRAOSSEOUS HEMANGIOMA: CASE REPORT - Merve Yelken Kendirci; Gürkan Ünsal; İlknur Özcan; Merva Soluk Tekkeşin (Sabiad)
Hemangiomas are defined as benign neoplasms originating from vascular endothelial tissue. Intraosseous hemangiomas are very rare and account for less than 1% of bone tumors. They are mostly seen in vertebras, skull bones and long bones. Intraosseous hemangiomas are very rare in jaws. Intraosseous hemangiomas are typically asymptomatic and grow slowly. In this case report, asymptomatic intraosseous hemangioma was found in the mandible and the patient was evaluated clinically, radiologically and histopathologically. A-69-year old male patient was referred to our clinic with a multilocular lesion. CBCT and MRI were evaluated for further examination. Histopathological examination revealed intraosseous hemangioma in the mandible.